2003
DOI: 10.1097/01.sap.0000095652.35806.c5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steroids on Edema, Ecchymosis, and Intraoperative Bleeding in Rhinoplasty

Abstract: A double-blind, randomized study was designed to determine the efficacy of dexamethasone in decreasing periorbital edema and ecchymosis after rhinoplasty. Sixty rhinoplasty patients undergoing hump resection and lateral osteotomy were included in the study and were divided into 6 groups: group 1 (n = 10), single dose of 8 mg intravenous (IV) dexamethasone 1 hour before the operation; group 2 (n = 10), single dose of 8 mg IV dexamethasone at the beginning of the operation; group 3 (n = 10), 3 doses of 8 mg IV d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 16 publications
2
75
1
2
Order By: Relevance
“…Moreover they did not report swelling increment on the 2nd day because they continued steroid use for 5 days and the infl ammatory response might be overcome and the increment of edema on the 2nd day would not appear. Kargi et al [14] designed different administration patterns of dexamethasone to assess Statistical analysis was performed using STATA (SE 8.2, StataCorp, College Station, TX, USA). Five percent was used as the threshold for statistical signifi cance.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover they did not report swelling increment on the 2nd day because they continued steroid use for 5 days and the infl ammatory response might be overcome and the increment of edema on the 2nd day would not appear. Kargi et al [14] designed different administration patterns of dexamethasone to assess Statistical analysis was performed using STATA (SE 8.2, StataCorp, College Station, TX, USA). Five percent was used as the threshold for statistical signifi cance.…”
Section: Methodsmentioning
confidence: 99%
“…Previous randomized controlled trials have implemented prednisone (4,17), methylprednisolone (2,9-11), betamethasone (2) and dexamethasone (2)(3)(4)(5)14,16), among others, and have suggested better results if high and repeated doses are given versus placebo, in most cases (1)(2)(3)(4)(5)9,10). Most reports present isolated findings of one type of steroid compared with placebo; two studies, however, have reported conflicting results.…”
Section: Discussionmentioning
confidence: 80%
“…Although no complications have been reported in different series (1,2,4,5,7,(9)(10)(11)(13)(14)(15), it is our opinion that we should consider the side effects that high doses of methylprednisolone could have if used frequently in our practice.…”
mentioning
confidence: 99%
“…[52] In the same line, Kargi et al, and Kara and Gokalan showed that the perioperative use of corticosteroids reduced edema and ecchymosis associated with rhinoplasty surgery. [53,54] In contrast, Hoffmann et al did not observe any increase either in the edema or the ecchymosis after rhinoplasty surgery. [55] Regarding orthognathic surgery, several investigations demonstrated that perioperative corticosteroid administration significantly reduced post-operative inflammation and edema.…”
Section: Management Of Post-operative Morbidities Associated With Maxmentioning
confidence: 85%